Electronic, electrical and optical properties of Ag doped CuO through modified Becke-Johnson exchange potential. (March 2019) - Absike, H.; Hajji, M.; Labrim, H.; Abbassi, A.; Ez-Zahraouy, H.
Abstract: This study examined the influence of the Ag doping concentration on the structural, electrical and optical properties of copper oxide (CuO), using the density functional theory DFT with Tran-Blaha modified Becke-Johnson (mBJ). Based on the optimized structural parameters, the structural properties, the band gaps, density of states (DOS), the profiles of the optical spectra and optical properties, including the real and imaginary parts of dielectric function, absorption coefficient, reflectivity and refractive index are obtained and showed a good agreement with experimental results. Beside this, our results indicate that CuO is an antiferromagnetic semiconductor material with an indirect gap about 1.99 eV. This increasing with decreasing Silver concentration. Furthermore, the absorption spectra display excellent physical behavior in the range of visible light which it is in good with agreement with many experimental data. In fact, this confirms the physical characteristics that can present CuO to be used as suitable absorbent material in solar cells. Highlights: Electronic, Electrical and Optical properties of Ag doped copper oxide (CuO). Properties of band structure, density of state, charge density and optical proprieties are investigated. Density functional theory are performed using mBJ method.